(untitled) (Economic studies journal, 2023)
The study aimed to identify the difficulties facing the Yaqeen Bank in granting Green Financing. The descriptive analytical method was used, as a questionnaire was designed and distributed to the study sample, which is a sample of bank employees. The Statistical Package for the Social Sciences (SPSS) program was used to analyze the primary data contained in the questionnaire. The study found that there are obstacles that prevent the Yaqeen Bank to grant Green Finance. These obstacles were represented in: obstacles related to expertise and competencies, legal and legislative obstacles, obstacles related to the directions and objectives of the bank, and obstacles related to the financial capacity of the bank. The study also reached a number of recommendations represented in: Working on paying attention to training and developing the bank’s staff, and developing the legal and legislative structure to keep pace with the development taking place in the banking industry in general and green financing in particular. The study also recommended motivating the bank’s senior management to provide green financing, the study also recommended the development of means to obtain sufficient funds to provide green financing, including the issuance of green Islamic Sukuk.